Driving Business Growth: Unveiling the Power of Innovation Management Through Bibliometric Analysis - Juracka Denis; Valaskova Katarina (Folia Oeconomica Stetinensia)
Every business activity involves the business environment. The faster rate of technology development has an impact on innovation management roles within the company as well as innovation approach methods. For these reasons, it is necessary to analyze innovation management in individual countries because it includes decisions made and actions done in relation to creating and implementing an innovation strategy. Every business operates in a certain atmosphere that is dynamic and has a constant impact on the business. Therefore, it is important to analyze and predict the development of the business environment.